POSSIBILITIES AND THERAPY LIMITATIONS IN A CASE OF ADRENOGENITAL SYNDROME - Alina Grama (Romanian Journal of Pediatrics, 2016)
Introduction. The adrenogenital syndrome with neonatal onset can manifest by repeated vomiting, dehydration and severe hydro-electrolytic disequilibria. The diagnostic approach, the metabolic reequilibration and the maintenance of the electrolytic balance in normal ranges by chronic treatment can be associated with difficulties. Objective. We present a case of adrenogenital syndrome with severe neonatal onset, evolution accompanied by different complications, but with a prognosis improved by the adequate chronic treatment. Material and method. A male child with small birth weight, was admitted in the Pediatrcs Clinic I, Targu-Mures, at the age of 3 weeks, with a severe clinic-biological syndrome by chronic vomiting and severe dehydration, and apparent macrogenitosomia. We performed a wide spectrum of investigations in acute phase, but also afterwards for the elaboration of the differential diagnosis. Results. We identified persistent hyponatremia and hypopotassemia, an increased level of 17-OH progesterone (44.96 ng/ml) and the cortisol under the normal limit (3 ug/dl). We discovered significantly increased concentrations of ACTH (103 pg/ml in the morning) and total serum cholesterol (186.72 ng/dl). The macromolecular analysis pointed out the heterozygote genotype for the following mutations: 12G, R356W, P453S. The adequate chronic treatment with cortisone improved the prognosis; at the age of 1 years and 5 months, he presents an adequate height, weight and psychomotor development. Conclusions. We fulfilled the conditions of the diagnosis of adrenogenital syndrome with neonatal onset in a heterozygote child. The small age the uncharacteristic symptomatology can be a burden for establishing an early diagnosis of adrenogenital syndrome.